Anaphylaxis to packaged foods in Australasia. (24th January 2018) - Zurzolo, Giovanni A; Allen, Katrina J; Peters, Rachel L; Tang, Mimi LK; Dharmage, Shyamali; de Courten, Maximilian; Mathai, Michael L; Campbell, Dianne E
Abstract : Aims: To examine reports of anaphylaxis in Australasia from consumption of packaged food products with or without precautionary allergen labelling (PAL), where the known allergen triggers were not a listed ingredient. Methods: A questionnaire was sent to all members of the Australasian Society of Clinical Immunology and Allergy ( n = 548). Participants were asked to complete a survey reporting whether they have had seen any patients over the last 3 months reporting anaphylaxis following ingestion of a packaged food where the suspected food allergen was not a listed ingredient. Results: Of the n = 548 members approached, n = 198 responded (response rate 36.1%).There were 14 reports of anaphylaxis to packaged foods (where the suspected allergen was not a listed ingredient), which met the case definition from a total of 198 respondents over the 9‐month period. Of those reactions, 50.0% (confidence interval 95% 21–78) were reported from foods that did not have a PAL statement, and 50.0% (confidence interval 95% 21–78) were due to peanuts. Conclusion: Anaphylaxis to undeclared allergens was not rare and did not appear to depend on whether the product was labelled with precautionary advice. There is currently no reliable labelling system that can inform food‐allergic consumers of safer food choices. Improvements in the regulation of food labelling with PAL are required.